Effect of soil properties on yield, quality and soil quality score of food crops - Turdimetov, Shakhobiddin; Khudayberdieva, Zarina; Uzaydullaev, Akmal; Kuzibekov, Sardor; Esanbayeva, Nasiba; Xo’jabekova, Dildora; Kudratov, Xoyitjan (International Journal of Aquatic Research and Environmental Studies, 2025)
The article presents the properties and characteristics of irrigated soils distributed in the Mirzachol oasis. Correlative relationships between soil properties, such as soil mechanical composition, humus content and salinity level, and yield of winter wheat, soybean, and its technological indicators have been determined. Based on the obtained yield indicators, the soil quality assessment for these crops was calculated. Calculation of crop yield based on soil quality scores, calculation of average soil quality score on the example of one array is also covered.